How Do Low-Income Enrollees in the Affordable Care Act Marketplaces Respond to Cost-Sharing? - Kurt Lavetti; Thomas DeLeire; Nicolas R. Ziebarth (Institute of Labor Economics (IZA), 2019)
The ACA requires insurers to provide cost-sharing reductions (CSRs) to low-income consumers on the marketplaces. We link 2013-2015 All-Payer Claims Data to 2004-2013 administrative hospital discharge data from Utah and exploit policy-driven differences in the value of CSRs that are solely determined by income. We find that enrollees with lower cost sharing have higher levels of health care spending, controlling for past health care use. We estimate the demand elasticity of total health care spending to be -0.10, but find larger elasticities for emergency room care, lifestyle drugs, and low-value care. We also find positive cross-price elasticities between outpatient and inpatient care.
Keywords: H24; H41; H43; H51; I11; I18; J32; J33; J68; 330; demand elasticities; health insurance; moral hazard; ACA; marketplaces; AV-variants; low-value care; lifestyle drugs; value-based CSRs; Utah